2017
DOI: 10.1111/cch.12475
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the school experiences of children and adolescents with serious chronic illness: a systematic meta‐review

Abstract: Students with chronic illness demonstrate mixed school experiences and outcomes that are often worse than students without chronic illness. Modifiable factors, such as students' engagement with school, may be novel yet appropriate targets of educational support to ensure that these students reach their full schooling potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
121
1
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(140 citation statements)
references
References 97 publications
(216 reference statements)
8
121
1
10
Order By: Relevance
“…Over recent decades, the number of children living with a chronic illness has increased significantly with an estimated 12% of young people aged 10–19 years having a long‐term health condition (DH, ; Leeman et al, ). However, they may experience poorer psychosocial and educational outcomes when compared with their healthy peers (Champaloux & Young, ; Lum et al, ; Nylander, Seidel, & Tindberg, ). Research exploring young peoples' experiences of living with different conditions has uncovered consistent themes.…”
Section: Introductionmentioning
confidence: 99%
“…Over recent decades, the number of children living with a chronic illness has increased significantly with an estimated 12% of young people aged 10–19 years having a long‐term health condition (DH, ; Leeman et al, ). However, they may experience poorer psychosocial and educational outcomes when compared with their healthy peers (Champaloux & Young, ; Lum et al, ; Nylander, Seidel, & Tindberg, ). Research exploring young peoples' experiences of living with different conditions has uncovered consistent themes.…”
Section: Introductionmentioning
confidence: 99%
“…School is an area of particular concern when evaluating disease/treatment-related risks and implications for pediatric patients, as evidence indicates that these youth experience suboptimal educational outcomes compared with healthy peers. [5][6][7] Despite the well-established need for educational interventions for students with a chronic illness [8][9][10] , prior to now, a tool did not exist to stratify risk and educational interventions in education based on the presence of an illness. The existing assessments in other psychosocial disciplines are limited in their ability to predict risk in education, as education is not the primary focus of those instruments.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic meta‐review, Lum and colleagues critiqued the available evidence examining the link between six chronic illnesses and children's and adolescents' school experiences and outcomes. They found that students with chronic illnesses, while demonstrating mixed results, often had worse school experiences and outcomes as compared with students without chronic illnesses (Lum et al, ). They suggest that, “An improved understanding of the factors that help to explain or mitigate this risk can help educators and health professionals deliver the most effective support.” In this paper, we aim to review, critique, and build on what is empirically known about such risk and protective factors.…”
Section: Introductionmentioning
confidence: 99%
“…and outcomes as compared with students without chronic illnesses (Lum et al, 2017). They suggest that, "An improved understanding of the factors that help to explain or mitigate this risk can help educators and health professionals deliver the most effective support."…”
mentioning
confidence: 99%